2014
DOI: 10.1002/oby.20975
|View full text |Cite
|
Sign up to set email alerts
|

The association of common polymorphisms in miR-196a2 with waist to hip ratio and miR-1908 with serum lipid and glucose

Abstract: Objective MicroRNAs (miRNAs) have been implicated in the regulation of cardiometabolic disorders. Given the crucial role of miRNAs in gene expression, genetic variation within miRNA genes is expected to affect miRNA function and substantially contribute to disease risk. Methods 2,320 variants in miRNA‐encoding sequences were systematically retrieved, and their associations with 17 cardiometabolic traits/diseases were investigated, using genome‐wide association studies (GWAS) on glycemic indices, anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Here, we used a genetic approach that is proven to be efficient and successful for identification of miRNAs involved in complex traits. 1923 In this approach, the starting point is a linkage between miRNA variants and the trait of interest. The main advantage of the genetic approach compared to miRNA expression profiling is that when a variant is associated with disease risk, it supports the idea that the miRNA may have a primary effect in the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we used a genetic approach that is proven to be efficient and successful for identification of miRNAs involved in complex traits. 1923 In this approach, the starting point is a linkage between miRNA variants and the trait of interest. The main advantage of the genetic approach compared to miRNA expression profiling is that when a variant is associated with disease risk, it supports the idea that the miRNA may have a primary effect in the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Foster, 8 Christopher J. Hammond, 9 Alex W. Hewitt, 10,11 René Höhn, 12,13 Pirro G. Hysi, 9 Jost Jonas, 14 Anthony P. Khawaja, 8,15 Andrew J. Lotery, 7 Stuart MacGregor, 16 David A. Mackey, 17 Paul Mitchell, 18 Louis R. Pasquale, 19,20 Francesca Pasutto, 21 Norbert Pfeiffer, 22 Ananth C. Viswanathanm, 8 Veronique Vitart, 23 Eranga N. Vithana, 1 Jie Jin Wang, 18 Janey L. Wiggs, 19 Robert Wojciechowski, 24–26 Tien Yin Wong, 13 and Terri L. Young 27 1 Singapore Eye Research Institute, Singapore National Eye Centre, Singapore. 2 Ophthalmology & Visual Sciences Academic Clinical Program (Eye ACP), Duke-NUS Medical School, Singapore. 3 Department of Ophthalmology, Yong Loo Lin School of Medicine, National University of Singapore, Singapore. 4 Menzies Institute for Medical Research, University of Tasmania, Hobart, Tasmania, Australia. 5 Department of Epidemiology and Biostatistics, Case Western Reserve University, Cleveland, Ohio, United States. 6 Department of Ophthalmology, Flinders University, Adelaide, Australia. 7 Clinical & Experimental Sciences, Faculty of Medicine, University of Southampton, Southampton, United Kingdom. 8 NIHR Biomedical Research Centre, Moorfields Eye Hospital NHS Foundation Trust and UCL Institute of Ophthalmology, London, United Kingdom. 9 Department of Twin Research and Genetic Epidemiology, King's College London, United Kingdom. 10 Centre for Eye Research Australia, University of Melbourne, Department of Ophthalmology, Royal Victorian Eye and Ear Hospital, Melbourne, Victoria, Australia. 11 School of Medicine, Menzies Institute for Medical Research, University of Tasmania, Hobart, Tasmania, Australia. 12 Department of Ophthalmology, University Medical Center Mainz, Mainz, Germany. 13 Department of Ophthalmology, Inselspital, University Hospital Bern, University of Bern, Switzerland. 14 Department of Ophthalmology, Medical Faculty Mannheim of the Ruprecht-Karls-University of Heidelberg, Mannheim, Germany. 15 Department of Public Health and Primary Care, Institute of Public Health, University of Cambridge School of Clinical Medicine, Cambridge, United Kingdom. 16 Statistical Genetics, QIMR Berghofer Medical Research Institute, Brisbane, Australia. 17 Lions Eye Institute, Centre for Ophthalmology and Visual Science, University of Western Australia, Perth, Western Australia, Australia. 18 Centre for Vision Research, Department of Ophthalmology and Westmead Institute for Medical Research, University of Sydney, Sydney, New South Wales, Australia. 19 Department of Ophthalmology, Harvard Medical School and Massachusetts Eye and Ear Infirmary, Boston, Massachusetts, United States. 20 Channing Division of Network Medicine, Brigham and Women's Hospital, Boston, Massachusetts, United States. 21 Institute of Human Genetics, Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), Erlangen, Germany. 22 Department of Ophthalmology, University Medical Center Mainz, Mainz, Germany. 23 Institute of Genetics and Molecular Medicine, Medical Research Council Human Genetics Unit, University of Edinburgh, Edinburgh, United King...…”
Section: International Glaucoma Genetics Consortium (Iggc) Membershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study identified that the low expression of miR-1908 predicted a poor prognosis in glioma (12). In addition, miR-1908 has also been associated with the prognosis of chordoma, hepatoma and melanoma (13)(14)(15)(16). miR-1908 has different functions in different cancer types, as it may target different genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variants that are located in the seed-matching regions of target genes may interfere with the interaction between miRNAs and their target genes, resulting in an altered expression level of the target transcript1718. More recently, we and others have been able to show a number of variants in genomic sequences encoding miRNAs or in the 3′ UTRs of miRNA target genes that contribute to phenotypic variations and disease risk1819202122. However, the association of such variants with the risk of AD has not yet been systematically investigated.…”
mentioning
confidence: 99%